Immediate Donor Site Complications after Anterior Cruciate Ligament Reconstruction with Bone-Patellar Tendon-Bone Autograft: 2 Case Reports. Issue 5 (28th May 2020) - Liu, Hsuan-Chih; Lin, Ching-Wei; Wu, Chung-Ta
With the increasing number of anterior cruciate ligament reconstructions (ACL-R), complications after reconstruction are likely to become more frequent. Patellar fracture is a rare but significant complication following ACL reconstruction when using a bone-patellar tendon-bone (BPTB) autograft. This case report presents 1 simple patellar fracture, 1 patellar comminuted fracture with associated patellar tendon rupture which occurred acutely after ACL reconstruction using BPTB graft. Methods: Case 1: 17-year-old female. Nondisplaced linear lateral pole patellar fracture was first noticed at post-op 6 weeks followed-up. There was no subjectively complaint issued by the patient after the operation. She was managed conservatively with closed follow up until the fracture had healed. Case 2: 37-year-old woman, 6 weeks after operation. The patient slipped on a wet floor and injured the operated knee joint. Patellar lower pole comminuted fracture with complete patella tendon tear was diagnosed. Open reduction and internal fixation of the fracture and patella tendon repair were performed. Results: Case 1: She achieved full fracture union at 3 months, is 76 months post-operatively. She is currently active in sports activities without any problem. Case 2: The fracture healed at 2 months; she has had full, active knee joint extension and full ROM of the knee joint at 3 months post-operatively. She is now 9 months after the primary ACL-R surgery, is well on track with our ACL-R rehabilitation program. Discussion: Case 1 fracture was believed to happen at the time of graft harvesting without our noticing. Case 2 had a fall and caused a more complicated donor site problem. Though rare, these complications cause major post-operative and rehabilitation problems. Closed follow-up, early detection with immediate intervention should be warranted after ACL-R surgeries.